47 patients with FLNA associated periventricular nodular heterotopia - Lange, Max; Kasper, Burkhard; Bohring, Axel; Rutsch, Frank; Kluger, Gerhard; Hoffjan, Sabine; Spranger, Stephanie; Behnecke, Anne; Ferbert, Andreas; Hahn, Andreas; Oehl-Jaschkowitz, Barbara; Graul-Neumann, Luitgard; et al. (Orphanet journal of rare diseases, 2015)
Heterozygous loss of function mutations within the Filamin A gene in Xq28 are the most frequent cause of bilateral neuronal periventricular nodular heterotopia (PVNH). Most affected females are reported to initially present with difficult to treat seizures at variable age of onset. Psychomotor development and cognition may be normal or mildly to moderately impaired. Distinct associated extracerebral findings have been observed and may help to establish the diagnosis including patent ductus arteriosus Botalli, progressive dystrophic cardiac valve disease and aortic dissection, chronic obstructive lung disease or chronic constipation. Genotype-phenotype correlations could not yet be established.
Gesehen am 09.06.2020